Efficacy of sesame (Sesamum indicum) root exudates against major weeds of pulse crops - KUMAR, LALIT; VARSHNEY, JAY G (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004–05 at Kanpur, Uttar Pradesh, to find out the effect of sesame (Sesamum indicum L.) allelochemicals on the germination and growth of prominent weeds grows in the winter legumes. Emulsion concentrate or emulsive water formulation developed from crystallized product of sesame root exudates showed consistent adverse effect on the germination and growth of prominent weeds found in food legumes. Emulsive water formulation at 240 mg/g not only delayed but also inhibited germination of lambsquarters (Chenopodium album L.) 80%, followed by scarlet pimpernel (Anagallis arvensis L.) 75%, white sweet clover (Melilotus alba L. Medik.) 65%, corn flurry (Spergula arvensis L.) 60%, fumitory (Fumaria parviflora Lam.) 55% and common vetch (Vicia sativa L.) 50% over the control. At 280 mg/g maximum inhibition in shoot biomass was observed in case of lambsquarters (85.8%), followed by fumitory (81.57%), common vetch (52.4%), corn flurry (49.27%), scarlet pimpernel (46.07%), and white sweet clover (41.93%) over the control. Whereas based on root biomass inhibition the toxicity trend of formulation was observed as lambasquarter by (89.28%), followed by corn flurry (83.33%), sweet clover (72.22%), common vetch (64.51%), fumitory (62.68%) and scarlet pimpernel (58.42%). Based on entire biomass inhibition, emulsive water formulation found more toxic to lambasquarters (86.02%), followed by fumitory (78.68%), common vetch (56.26%), corn flurry (50.42%), white sweet clover (49.07%) and scarlet pimpernel (48.25%) over control at same concentration.